STRATEGIC ADAPTATIONS IN CULTURAL MANAGEMENT: ENHANCING ORGANISATIONAL RESILIENCE AND INNOVATION IN ROME'S CREATIVE INDUSTRIES - Pastore, Lavinia; Corvo, Luigi (Piccola Impresa / Small Business, 2025)
Purpose. This study explores the dynamic interplay between organisational resilience and innovation within Rome's cultural and creative industries (CCI) amid significant urban dynamics and cultural policy reforms. The research aims to understand deeper systemic challenges and transformations affecting CCIs and uncover strategies that enhance organisational resilience and foster innovation. Design/methodology/approach. The study employs a mixed-methods approach to synthesise quantitative data from a specially designed questionnaire and derive qualitative insights from 33 semi-structured interviews with key stakeholders in Rome’s CCI. This methodological mix, supported by NVivo software for data integration and analysis, facilitates a holistic understanding of how cultural organisations navigate both longstanding and emergent challenges. Findings. The findings reveal significant organisational agility across Rome’s CCIs, with entities exhibiting various degrees of innovation in response to shifting environmental pressures. Their strategic pivot towards more sustainable and resilient operational frameworks challenges traditional views on innovation that are linear and prescriptive. Practical and Social Implications. The study underscores the importance of supportive infrastructure and financial mechanisms in the sustainability and growth of CCIs. Further, it explores how cultural organisations transform these challenges into opportunities for systemic growth and enhancing sectoral vitality, thereby emphasising a nuanced understanding of the complex interdependencies between cultural policy, organisational resilience, and innovation. Originality of the study. This study highlights how adaptive resilience and targeted support can coalesce to foster vibrant and sustainable urban cultural ecosystems and provides a fresh perspective on managing cultural industries through a crisis, emphasising the role of innovation and strategic adaptation in sustaining cultural vitality.